Good Corporate Governance Dan Media Exposure Terhadap Carbon Emission Disclosure Dengan Pemoderasi Kinerja Lingkungan - Muhamad Dicky Aprizal; Iin Rosini; Suripto Suripto (CV. ULIL ALBAB CORP, 2024)
This research aims to provide empirical evidence on the influence of Good Corporate Governance and Media Exposure on Carbon Emission Disclosure, with Environmental performance as a moderating variable. The population in this study consists of companies listed in the Top 50 Big Cap Public Listed Companies on the Indonesia Stock Exchange from 2018 to 2022. The sample was determined using a purposive sampling technique, resulting in 20 companies with a total of 100 observational data points. The analytical technique and hypothesis testing were conducted using panel data regression analysis through Eviews-12. The results indicate that Good Corporate Governance has a negative effect on Carbon Emission Disclosure, while Media Exposure has a positive effect on Carbon Emission Disclosure. Environmental performance moderates the relationship between Good Corporate Governance and Carbon Emission Disclosure; however, it does not moderate the relationship between Media Exposure and Carbon Emission Disclosure.